Burnout Digital : Keterhubungan Konstan pada Mental Gen Z - Tita Ramadhani Syahwa; Rendi Bimayuda; Ati Kusmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
These findings confirm that digital burnout is a serious mental health issue that requires a holistic approach to addressing it. In addition to internal factors such as low self-awareness regarding digital media usage limits, external factors such as academic pressure, high productivity demands, and a hustle culture also exacerbate digital burnout in Generation Z. They often feel trapped in a cycle of hyper-connectivity, where digital media is not only a communication tool but also a source of social validation and self-existence. This dependency has the potential to form compulsive behavioral patterns that are difficult to break, even when individuals begin to experience the negative impacts. Coping strategies used by Generation Z vary, from digital detoxes and screen time management to seeking social support. However, the effectiveness of these strategies depends heavily on individual awareness and support from their surrounding environment, including family, school, and the digital community itself. Several studies also recommend the application of digital mindfulness, namely full awareness in using technology wisely, as one way to reduce the symptoms of digital burnout. Digital literacy and mental health education are also important keys in equipping Generation Z to manage the pressures of digital media in a healthy and sustainable manner. Thus, it is crucial for policymakers, educators, and mental health service providers to work together to create a digital ecosystem that is more supportive and focused on the well-being of young users. Further research is recommended to explore technology-based interventions with a humanistic approach, to balance the benefits and risks in this era of limitless connectivity. Collaborative cross-sector efforts are essential to build collective awareness of the importance of digital balance for the mental health of Generation Z.